Whole body cardiovascular magnetic resonance imaging to stratify symptomatic and asymptomatic atherosclerotic burden in patients with isolated cardiovascular disease. Issue 1 (December 2016) - Weir-McCall, Jonathan; Duce, Suzanne; Gandy, Stephen; Matthew, Shona; Martin, Patricia; Cassidy, Deirdre; McCormick, Lynne; Belch, Jill; Struthers, Allan; Colhoun, Helen; Houston, J.
Abstract Background The aim of this study was to use whole body cardiovascular magnetic resonance imaging (WB CVMR) to assess the heart and arterial network in a single examination, so as to describe the burden of atherosclerosis and subclinical disease in participants with symptomatic single site vascular disease. Methods 64 patients with a history of symptomatic single site vascular disease (38 coronary artery disease (CAD), 9 cerebrovascular disease, 17 peripheral arterial disease (PAD)) underwent whole body angiogram and cardiac MR in a 3 T scanner. The arterial tree was subdivided into 31 segments and each scored according to the degree of stenosis. From this a standardised atheroma score (SAS) was calculated. Cine and late gadolinium enhancement images of the left ventricle were obtained. Results Asymptomatic atherosclerotic disease with greater than 50 % stenosis in arteries other than that responsible for their presenting complain was detected in 37 % of CAD, 33 % of cerebrovascular and 47 % of PAD patients. Unrecognised myocardial infarcts were observed in 29 % of PAD patients. SAS was significantly higher in PAD patients 24 (17.5-30.5) compared to CAD 4 (2–11.25) or cerebrovascular disease patients 6 (2-10) (ANCOVA p < 0.001). Standardised atheroma score positively correlated with age (β 0.36 p = 0.002), smoking status (β 0.34 p = 0.002), and LV mass (β -0.61 p = 0.001) on multiple linear regression. Conclusion WB CVMR is an effective method for the stratification of cardiovascular disease. The high prevalence of asymptomatic arterial disease, and silent myocardial infarctions, particularly in the peripheral arterial disease group, demonstrates the importance of a systematic approach to the assessment of cardiovascular disease.